2003
DOI: 10.1167/iovs.03-0590
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Corneal Epithelial Cell Death by Activation of Potassium Channels

Abstract: The results indicate that UV irradiation induces superactivity of K+ channels in the membrane is an early event mediating signaling transduction and resulting in corneal epithelial cell death in response to UV irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…(Soliven et al, 1991;Dubois and Rouzaire-Dubois, 1993;Bright et al, 1994;Duprat et al, 1995;Szabo et al, 1996;Wang et al, 1999a,b;Lu et al, 2003;Gao et al, 2004;Guo et al, 2005). For example, we, as well as other researchers, have shown that stimulation of K + channel activity and dramatic loss of intracellular K + can result in apoptosis in the corneal epithelium, neurons, myeloblastic ML-1 cells, and other cell types (Schulz et al, 1996;Eldadah et al, 1997;Yu et al, 1997;Wang et al, 1999aWang et al, ,2003Lu et al, 2003;Trimarchi et al, 2002;Remillard and Yuan, 2004). It seems that there are dual functions of K + channels involving cell proliferation regulated by epidermal growth factor (EGF) (Lu et al, 2001a) and playing a role in mediating cell death induced by UV irradiation (Wang et al, 1999aLu et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…(Soliven et al, 1991;Dubois and Rouzaire-Dubois, 1993;Bright et al, 1994;Duprat et al, 1995;Szabo et al, 1996;Wang et al, 1999a,b;Lu et al, 2003;Gao et al, 2004;Guo et al, 2005). For example, we, as well as other researchers, have shown that stimulation of K + channel activity and dramatic loss of intracellular K + can result in apoptosis in the corneal epithelium, neurons, myeloblastic ML-1 cells, and other cell types (Schulz et al, 1996;Eldadah et al, 1997;Yu et al, 1997;Wang et al, 1999aWang et al, ,2003Lu et al, 2003;Trimarchi et al, 2002;Remillard and Yuan, 2004). It seems that there are dual functions of K + channels involving cell proliferation regulated by epidermal growth factor (EGF) (Lu et al, 2001a) and playing a role in mediating cell death induced by UV irradiation (Wang et al, 1999aLu et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
“…Each of these responses is dependent on K + channel activation. Therefore, corneal epithelial renewal, which is a result of a balance between cell proliferation, apoptosis and differentiation, is dependent on K + channel activation by stimuli that affect each of these responses Wang et al, 2003). There is one type of K + channels in corneal epithelial cells with characteristics similar to Kv3.4 channels.…”
Section: Expression Of Kv Channels In Corneal Epithelial Cellsmentioning
confidence: 99%
See 3 more Smart Citations